2021
DOI: 10.1177/1056789521991196
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid bacteria mediated cemented sand: Microcharacterization, permeability, strength, shear wave velocity, stress-strain, and durability

Abstract: Microbially induced calcite precipitation (MICP), a sustainable approach for sand biocementation, was investigated in previous studies based on metabolic activity of individual microorganisms. The individual bacteria, specifically Sporosarcina pasteurii (SP), Bacillus subtilis (BS), and Lysinibacillus sphaericus (LS), were found capable enough for sand biocementation. However, present study investigates synergistic effects of using bacterial-hybrids on cementation and consequent improvement in sand properties.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 68 publications
(90 reference statements)
0
8
0
Order By: Relevance
“…Ultrasonic pulse velocity (UPV) tests were performed to analyse the rock behaviour of biotreated sand samples, with Figure A2b showing a test performed on UCS biotreated desert sample. According to the literature, the shear wave velocity of poorly graded sand ranges from 149 to 303 m/s (Sharma et al, 2021c). Figure 5 shows the UPV values for biotreated desert sand samples for different treatment conditions and was found that the maximum values for AG, SA and P were 1579, 1490 and 1400 m/s, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Ultrasonic pulse velocity (UPV) tests were performed to analyse the rock behaviour of biotreated sand samples, with Figure A2b showing a test performed on UCS biotreated desert sample. According to the literature, the shear wave velocity of poorly graded sand ranges from 149 to 303 m/s (Sharma et al, 2021c). Figure 5 shows the UPV values for biotreated desert sand samples for different treatment conditions and was found that the maximum values for AG, SA and P were 1579, 1490 and 1400 m/s, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The coefficient of variation was less than 19 for all layers and combinations, which was acceptable as calcite-content formation depends on many factors, such as type of bacteria, bacterial density, crystal formation, temperature, and pH value. Various studies [6] have found that the coefficient of variation of more than 21 was within the acceptable limits. Figure 9 shows the percentage of calcite content for different treatment combinations for all three layers.…”
Section: Caco 3 Precipitationmentioning
confidence: 90%
“…The reaction between carbonate ions and calcium ions started, and precipitation of calcite crystals occurred. Sharma et al (2021) [6] suggested that the stopped-flow pouring method was more effective for enhancing uniformity in calcite formation from top to bottom than the continuous-flow pouring method. After every 24 h, the cementation solution was drained out using a discharge nozzle (a bottle flap cap), and a freshly prepared cementation solution was provided after closing all flaps of the bottles.…”
Section: Micp-treatment Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The specimens treated with this combination resulted in 12-13.6% calcite precipitation, irrespective of the bacteria augmentation. Sharma et al (2021a) demonstrated that the samples treated with 0.50 M concentration using 12 h treatment cycle up to 18 days resulted in 2333 kPa unconfined compressive strength and 437 kPa split tensile strength with 96.6% hydraulic conductivity reduction. The similar biocemented specimen with 12% calcite content also showed rock-like (similar to sandstone) behavior and resulted in ultrasonic pulse wave velocity 2670 m/s.…”
Section: Effect Of Bacteria and Cementation Media Concentration On Calcite Precipitationmentioning
confidence: 99%